Wear-resistant cable material and preparation method thereof
By mixing and melt blending polypropylene resin with modified nanosilicon dioxide, glass fiber and lubricant, a modified polypropylene masterbatch was prepared, and a wear-resistant cable material was prepared through melt spinning process, which solved the problems of insufficient wear resistance and poor flame retardant performance of traditional cables in high wear environments, and achieved high-performance cable material.
Patent Information
- Application Number
- CN202411634716.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-15
- Publication Date
- 2025-03-14
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
Traditional polypropylene cables are not wear-resistant in harsh environments, and polypropylene has a low oxygen index, poor flame retardant performance, and there is a risk of combustion.
Modified polypropylene masterbatch was prepared by mixing and melt blending the polypropylene resin with modified nanosilica, glass fibers and lubricants, and wear-resistant cable material was prepared by melt spinning.
It significantly improves the wear resistance, oxygen resistance, flame retardancy and mechanical properties of cable materials, ensures stable performance in high wear environments and reduces combustion risks.
Smart Images

Figure BDA0005136858970000021 
Figure BDA0005136858970000031 
Figure BDA0005136858970000041
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of cables, and in particular, relates to a wear-resistant cable material and a preparation method thereof. Background Art
[0002] Cable is a kind of rope used for fixing, pulling, lifting, towing and other purposes. It has the properties of tensile resistance, impact resistance, wear resistance, flexibility and softness, and is widely used in many fields such as ships, construction, industry, agriculture, and fisheries. In the past, cotton, linen and steel cables were commonly used as cable materials, but these materials have their own shortcomings. The strength of cotton and linen is not high, and the flexibility of steel wire is not good. Therefore, most of the current cables are made of synthetic fibers. In addition to light weight, high strength, good impact resistance and wear resistance, synthetic fiber cables also have the advantages of corrosion resistance, mildew resistance, and insect resistance. Common synthetic fibers include nylon, polypropylene, vinylon, polyester, etc. Among them, polypropylene is also called polypropylene fiber. Polypropylene is a thermoplastic synthetic resin with excellent performance. It has chemical resistance, heat resistance, and electrical insulation. Because it has high crystallinity and good mechanical properties, polypropylene has excellent wear resistance, and its weight is light and its specific gravity is less than water. It can float on the water surface, and it is convenient and safe to operate. It is a high-quality cable material.
[0003] As people's needs continue to increase, in high-wear and harsh environments such as industry, national defense, offshore oil, offshore fishing, offshore towing, ship mooring, lifting and transportation, construction, mining, sports, etc., the wear resistance of traditional polypropylene cables can no longer meet people's needs. Polypropylene is an organic polymer material with a low oxygen index, poor flame retardant properties, and a risk of burning. Therefore, it is urgent to solve the above problems to meet higher demands in the field of cable technology. Summary of the invention
[0004] The purpose of the present invention is to overcome the defects of the prior art and provide a wear-resistant cable material and a preparation method thereof.
[0005] The purpose of the present invention can be achieved through the following technical solutions:
[0006] A method for preparing a wear-resistant cable material comprises the following steps:
[0007] A1. Dry the polypropylene resin in a drying oven at 100° C. for 12 h, add the dried polypropylene resin, modified nano-silicon dioxide, glass fiber and lubricant into a mixer and stir for 30 min, then add them into a twin-screw extruder, melt blend and extrude to obtain a modified polypropylene masterbatch;
[0008] A2. The modified polypropylene masterbatch obtained in step A1 is melt-spun, and the filaments are formed by cooling and blowing, cooling, solidifying, and winding to obtain a wear-resistant cable material.
[0009] Furthermore, the raw materials are calculated in parts by weight as follows: 80-100 parts of polypropylene resin, 12-28 parts of modified nano-silicon dioxide, 15-25 parts of glass fiber, and 3-5 parts of lubricant.
[0010] Furthermore, the lubricant is one of magnesium stearate and zinc stearate.
[0011] With polypropylene as the matrix, the cable material is endowed with certain wear resistance and mechanical properties; the added glass fiber as a filling material can greatly enhance the mechanical properties of the cable material.
[0012] Furthermore, the modified nano-silicon dioxide is prepared by the following steps:
[0013] S1. Disperse nano-silica in a three-necked flask filled with ethanol aqueous solution, add 3-aminopropyltrimethoxysilane (silane coupling agent KH-540) after ultrasonic treatment for 10 minutes, slowly heat to 65°C under strong mechanical stirring, react for 6 hours, cool to room temperature after the reaction, take the filter residue after suction filtration, wash it with anhydrous ethanol for 3-4 times, and dry it in a vacuum oven at 100°C to obtain intermediate 1; the ratio of nano-silica, ethanol aqueous solution and 3-aminopropyltrimethoxysilane is 1g:100mL:4.3g;
[0014] There are many -OH groups on the surface of nano-silica, which can introduce -NH2 active groups by reacting with KH-540, providing active sites for subsequent reactions to obtain intermediate 1. The specific reaction process is shown below:
[0015]
[0016] S2. In a three-necked flask equipped with a stirring device, the intermediate 1 is mixed with N,N-dimethylformamide (DMF), and ultrasonic treatment is performed for 30 minutes to make the intermediate 1 evenly dispersed, and then piperidine (condensation agent) and 3,5-di-tert-butyl-4-hydroxybenzaldehyde are added, and the mixture is kept warm in a water bath at 60°C for 8 hours. After the reaction is completed, the mixture is filtered, washed with anhydrous ethanol 3-4 times, and dried in an oven to obtain the intermediate 2; the ratio of the amount of the intermediate 1, N,N-dimethylformamide, piperidine, and 3,5-di-tert-butyl-4-hydroxybenzaldehyde is 1g:100mL:15mL:6.2g;
[0017] The amino group on the surface of intermediate 1 condenses with the aldehyde group on 3,5-di-tert-butyl-4-hydroxybenzaldehyde to form an imine group (C=N Schiff base structure) to obtain intermediate 2; the specific reaction process is as follows:
[0018]
[0019] S3, add 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide (DOPO) and toluene into a three-necked flask equipped with a stirring device, stir for 30 minutes under nitrogen protection, add half of the amount of phosphorus pentasulfide (P2S5), heat to 65°C, react for 4 hours, continue to add the other half of the amount of phosphorus pentasulfide, react at 55°C for 10 hours, complete the reaction, filter, remove the solvent from the filtrate under reduced pressure, dissolve it with chloroform, add saturated sodium bicarbonate solution dropwise under nitrogen protection, continue stirring for 15 minutes, let stand for stratification, take the organic phase and remove the solvent by reduced pressure distillation to obtain intermediate 3; the ratio of DOPO, toluene and phosphorus pentasulfide is 21.6g:100mL:11.2g;
[0020] DOPO reacts with phosphorus pentasulfide to introduce sulfur into the structure of DOPO to obtain intermediate 3. The specific reaction process is as follows:
[0021]
[0022] S4. In a three-necked flask equipped with a stirring device, mix the intermediate 2 with N,N-dimethylformamide, and ultrasonically treat for 30 minutes to make the intermediate 2 evenly dispersed. Then add the intermediate 3 and azobisisobutyronitrile (AIBN), stir magnetically for 2 hours, put it in a 70°C water bath for ultrasonication for 2 hours, then remove the water bath and stir magnetically at room temperature for 8 hours, filter, wash with anhydrous ethanol 3-4 times, dry, and grind to obtain modified nano-silica; the ratio of the amount of intermediate 2, N,N-dimethylformamide, intermediate 3, and azobisisobutyronitrile is 1g:100mL:5.1g:0.2g;
[0023] Under the catalysis of azobisisobutyronitrile, intermediate 2 reacts with intermediate 3 to obtain modified nano-silica; the specific reaction process is as follows:
[0024]
[0025] Nano-silicon dioxide has excellent wear resistance and strength. By modifying it and grafting organic molecular chains with it by chemical bonding, that is, forming an organic layer on its surface, the interfacial compatibility between the modified nano-silicon dioxide and the polypropylene matrix can be greatly improved, thereby promoting the uniform dispersion of the modified nano-silicon dioxide in the matrix, so that the performance of the modified nano-silicon dioxide can be fully exerted, and the wear resistance and mechanical properties of the matrix can be greatly improved; in addition, the modified nano-silicon dioxide molecules also contain DOPO structure, sulfur element and hindered phenol structure, among which DOPO is an environmentally friendly flame retardant with the advantages of high efficiency and low toxicity, and good thermal stability. The flame retardant has strong durability and can enhance the flame retardant properties of the matrix; the introduced sulfur element can release strong acids such as sulfuric acid under high temperature conditions, promote the dehydration of the substrate into carbon, and can also exert excellent flame retardant properties in the condensed phase, and can play a synergistic role with DOPO to greatly enhance the flame retardant properties of the matrix; the introduced hindered phenol can provide active hydrogen atoms to capture peroxyl radicals, which can not only greatly enhance the antioxidant properties of the matrix, but also act as an antioxidant in the production process, avoiding the addition of additional antioxidants and affecting the homogeneity of the matrix; finally, the modified nano-silica molecules contain benzene rings, which are rigid structures and can further enhance the wear resistance of the matrix;
[0026] It should be added that nano-silica grafted with organic molecular chains can prevent the migration and seepage of small organic molecules and improve the durability of performance.
[0027] Beneficial effects of the present invention:
[0028] 1. The cable material prepared by the present invention uses polypropylene as a matrix, which gives the cable material certain wear resistance and mechanical properties;
[0029] 2. The added glass fiber can further enhance the mechanical properties of the cable material;
[0030] 3. By modifying nano-silica, compared with ordinary nano-silica, it has better compatibility with the polypropylene matrix, can greatly enhance the wear resistance, oxidation resistance, flame retardancy and mechanical properties of the cable material, and the performance is long-lasting and stable, and not easy to fall off;
[0031] Therefore, the cable material prepared by the present invention has excellent mechanical properties, stable and efficient wear resistance, oxidation resistance and flame retardancy, and has important application value in the field of cable technology. DETAILED DESCRIPTION
[0032] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0033] Embodiment 1
[0034] Preparation of modified nano-silica:
[0035] S1. Disperse 1 g of nano-silica in a three-necked flask containing 100 mL of ethanol aqueous solution, and after ultrasonication for 10 min, add 4.3 g of 3-aminopropyltrimethoxysilane, slowly heat to 65 ° C under strong mechanical stirring, react for 6 h, and cool to room temperature after the reaction. After filtration, take the filter residue, wash it with anhydrous ethanol 4 times, and dry it in a vacuum oven at 100 ° C to obtain intermediate 1;
[0036] S2. In a three-necked flask equipped with a stirring device, 1 g of intermediate 1 was mixed with 100 mL of N,N-dimethylformamide, and ultrasonically treated for 30 min to make the intermediate 1 evenly dispersed. Then, 15 mL of piperidine and 6.2 g of 3,5-di-tert-butyl-4-hydroxybenzaldehyde were added, and the mixture was kept warm in a water bath at 60 ° C for 8 h. After the reaction was completed, the mixture was filtered, washed with anhydrous ethanol for 3 times, and dried in an oven to obtain intermediate 2;
[0037] S3, 21.6g 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide and 100mL toluene were added to a three-necked flask equipped with a stirring device, and stirred for 30min under nitrogen protection, and then 5.6g phosphorus pentasulfide was added, and the mixture was heated to 65°C. After reacting for 4h, 5.6g phosphorus pentasulfide was added, and the mixture was reacted at 55°C for 10h. After the reaction was completed, the mixture was filtered, and the solvent was removed from the filtrate under reduced pressure, and the mixture was dissolved in chloroform. A saturated sodium bicarbonate solution was added dropwise under nitrogen protection, and the mixture was stirred for 15min. The mixture was allowed to stand for stratification, and the organic phase was distilled under reduced pressure to remove the solvent to obtain intermediate 3;
[0038] S4. In a three-necked flask equipped with a stirring device, mix 1 g of intermediate 2 with 100 mL of N,N-dimethylformamide, and perform ultrasonic treatment for 30 min to evenly disperse intermediate 2. Then add 5.1 g of intermediate 3 and 0.2 g of azobisisobutyronitrile, and perform magnetic stirring for 2 h. Place the mixture in a 70°C water bath and perform ultrasonic treatment for 2 h. Remove the water bath and perform magnetic stirring at room temperature for 8 h. Filter the mixture, wash it three times with anhydrous ethanol, dry it, and grind it to obtain modified nano-silica.
[0039] Embodiment 2
[0040] Preparation of modified nano-silica:
[0041] S1. Disperse 2 g of nano-silica in a three-necked flask filled with 200 mL of ethanol aqueous solution, and after ultrasonication for 10 min, add 8.6 g of 3-aminopropyltrimethoxysilane, slowly heat to 65 ° C under strong mechanical stirring, react for 6 h, cool to room temperature after the reaction, filter and take the filter residue, wash it with anhydrous ethanol 4 times, and dry it in a vacuum oven at 100 ° C to obtain intermediate 1;
[0042] S2. In a three-necked flask equipped with a stirring device, 2 g of intermediate 1 was mixed with 200 mL of N,N-dimethylformamide, and ultrasonically treated for 30 min to make the intermediate 1 evenly dispersed. Then, 30 mL of piperidine and 12.4 g of 3,5-di-tert-butyl-4-hydroxybenzaldehyde were added, and the mixture was kept warm in a water bath at 60 ° C for 8 h. After the reaction was completed, the mixture was filtered, washed with anhydrous ethanol for 3 times, and dried in an oven to obtain intermediate 2;
[0043] S3, 43.2g 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide and 200mL toluene were added to a three-necked flask equipped with a stirring device, and stirred for 30min under nitrogen protection, and then 11.2g phosphorus pentasulfide was added, and the mixture was heated to 65°C. After reacting for 4h, 11.2g phosphorus pentasulfide was added, and the mixture was reacted at 55°C for 10h. After the reaction was completed, the mixture was filtered, and the solvent was removed from the filtrate under reduced pressure, and the mixture was dissolved in chloroform. A saturated sodium bicarbonate solution was added dropwise under nitrogen protection, and after the addition was completed, the mixture was stirred for 15min, and then the mixture was allowed to stand for stratification. The organic phase was taken and the solvent was removed by distillation under reduced pressure to obtain intermediate 3;
[0044] S4. In a three-necked flask equipped with a stirring device, mix 2 g of intermediate 2 with 200 mL of N,N-dimethylformamide, and perform ultrasonic treatment for 30 min to evenly disperse intermediate 2. Then add 10.2 g of intermediate 3 and 0.4 g of azobisisobutyronitrile, and stir magnetically for 2 h. Place in a 70°C water bath and perform ultrasonic treatment for 2 h. Remove the water bath and perform magnetic stirring at room temperature for 8 h. Filter, wash with anhydrous ethanol 4 times, dry, and grind to obtain modified nano-silica.
[0045] Embodiment 3
[0046] A1. Dry 80 g of polypropylene resin in a drying oven at 100° C. for 12 h, add the dried polypropylene resin, 12 g of modified nano-silicon dioxide obtained in Example 1, 15 g of glass fiber and 3 g of magnesium stearate into a mixer and stir for 30 min, then add the mixture into a twin-screw extruder, melt blend and extrude to obtain a modified polypropylene masterbatch;
[0047] A2. The modified polypropylene masterbatch obtained in step A1 is melt-spun, and the filaments are formed by cooling and blowing, cooling, solidifying, and winding to obtain a wear-resistant cable material.
[0048] Embodiment 4
[0049] A1, drying 90g of polypropylene resin in a drying oven at 100°C for 12h, adding the dried polypropylene resin, 20g of modified nano-silicon dioxide obtained in Example 2, 20g of glass fiber and 4g of zinc stearate into a mixer and stirring for 30min, then adding the mixture into a twin-screw extruder, melt blending and extruding to obtain a modified polypropylene masterbatch;
[0050] A2. The modified polypropylene masterbatch obtained in step A1 is melt-spun, and the filaments are formed by cooling and blowing, cooling, solidifying, and winding to obtain a wear-resistant cable material.
[0051] Embodiment 5
[0052] A1. Dry 100 g of polypropylene resin in a drying oven at 100° C. for 12 h, add the dried polypropylene resin, 28 g of modified nano-silicon dioxide obtained in Example 2, 25 g of glass fiber and 5 g of zinc stearate into a mixer and stir for 30 min, then add the mixture into a twin-screw extruder, melt blend and extrude to obtain a modified polypropylene masterbatch;
[0053] A2. The modified polypropylene masterbatch obtained in step A1 is melt-spun, and the filaments are formed by cooling and blowing, cooling, solidifying, and winding to obtain a wear-resistant cable material.
[0054] Comparative Example 1
[0055] Ordinary nano-silica of equal mass was used to replace the modified nano-silica in Example 5, and the remaining steps were the same as those in Example 5 to obtain a cable material.
[0056] Comparative Example 2
[0057] A commercially available wear-resistant polypropylene masterbatch is used for melt spinning, and the filaments are subjected to cooling blowing, cooling, solidification, and winding to obtain a cable material.
[0058] Embodiments 3, 4, 5, and comparative examples 1 and 2 were made into corresponding shapes to be tested according to different test standards, and the following performance tests were performed:
[0059] The national standard GB / T 14337-2008 "Test method for tensile properties of chemical staple fibers" was used to measure the breaking strength;
[0060] The sample was placed in a xenon lamp aging test chamber for accelerated aging for 14 days. The aging conditions were air atmosphere, xenon lamp wavelength 280-800nm, and irradiation intensity 550W / m 2 , test the breaking strength of the sample after aging (GB / T 14337-2008), and calculate the change in breaking strength; breaking strength retention rate = breaking strength after test / breaking strength before test × 100%;
[0061] The wear resistance is determined using the national standard GB / T 3960-2016 "Test methods for sliding friction and wear of plastics";
[0062] The limiting oxygen index was determined using the national standard GB / T 8924-2005 "Fiber-reinforced plastic combustion performance test method oxygen index method", and then the limiting oxygen index of Examples 3, 4, and 5 was determined after standing at room temperature for 180 days;
[0063] The measured results are shown in the following table:
[0064]
[0065] It can be seen from the above table that the mechanical properties, wear resistance, oxidation resistance and flame retardancy of the cable material prepared in the embodiment of the present invention are higher than those of the control example, and the performance is still excellent after 180 days, which has important application value in the field of cable technology.
[0066] In the description of the specification, the description with reference to the terms "one embodiment", "example", "specific example", etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representation of the above terms does not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described can be combined in any one or more embodiments or examples in a suitable manner.
[0067] The above contents are merely examples and explanations of the present invention. Those skilled in the art may make various modifications or additions to the specific embodiments described or replace them in a similar manner. As long as they do not deviate from the invention or exceed the scope defined by the claims, they shall all fall within the protection scope of the present invention.
Claims
1. A method for preparing a wear-resistant cable material, characterized in that: The following steps are involved: A1. Dry the polypropylene resin, add the dried polypropylene resin, modified nano-silicon dioxide, glass fiber and lubricant into a mixer and stir for 30 minutes, then add them into a twin-screw extruder, melt blend and extrude to obtain a modified polypropylene masterbatch; A2. The modified polypropylene masterbatch obtained in step A1 is melt-spun, and the filaments are formed by cooling and blowing, cooling, solidifying, and winding to obtain a wear-resistant cable material.
2. The method for preparing a wear-resistant cable material according to claim 1, characterized in that: The modified nano silicon dioxide is prepared by the following steps: S1. Disperse nano-silica in a three-necked flask filled with ethanol aqueous solution, and after ultrasonication for 10 minutes, add 3-aminopropyltrimethoxysilane, slowly heat to 65°C under stirring, react for 6 hours, cool to room temperature after the reaction, filter and collect the residue, wash and dry to obtain intermediate 1; S2, mixing intermediate 1 with N,N-dimethylformamide, ultrasonically treating for 30 min, then adding piperidine and 3,5-di-tert-butyl-4-hydroxybenzaldehyde, keeping warm in a water bath at 60°C for 8 h, the reaction is completed, filtered, washed, and dried in an oven to obtain intermediate 2; S3, 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide and toluene were added to a three-necked flask, stirred for 30 minutes under nitrogen protection, half of the amount of phosphorus pentasulfide was added, and the mixture was heated to 65°C. After reacting for 4 hours, the other half of the amount of phosphorus pentasulfide was added, and the mixture was reacted at 55°C for 10 hours. After the reaction was completed, the mixture was filtered, the solvent was removed from the filtrate under reduced pressure, and the mixture was dissolved in chloroform. A saturated sodium bicarbonate solution was added dropwise under nitrogen protection. After the addition was completed, the mixture was stirred for 15 minutes, and the mixture was allowed to stand for stratification. The organic phase was taken and distilled under reduced pressure to obtain intermediate 3; S4. Mix intermediate 2 with N,N-dimethylformamide, and perform ultrasonic treatment for 30 minutes to make intermediate 2 evenly dispersed. Then add intermediate 3 and azobisisobutyronitrile, and stir magnetically for 2 hours. Place in a 70°C water bath and perform ultrasonic treatment for 2 hours. Remove the water bath and perform magnetic stirring at room temperature for 8 hours. Filter, wash, dry, and grind to obtain modified nano-silica.
3. The method for preparing a wear-resistant cable material according to claim 2, characterized in that: In step S1, the ratio of the amount of nano-silica, the ethanol aqueous solution, and 3-aminopropyltrimethoxysilane is 1 g:100 mL:4.3 g.
4. The method for preparing a wear-resistant cable material according to claim 2, characterized in that: In step S2, the ratio of the amount of intermediate 1, N,N-dimethylformamide, piperidine, and 3,5-di-tert-butyl-4-hydroxybenzaldehyde is 1 g:100 mL:15 mL:6.2 g.
5. The method for preparing a wear-resistant cable material according to claim 2, characterized in that: In step S3, the ratio of DOPO, toluene and phosphorus pentasulfide is 21.6 g:100 mL:11.2 g.
6. The method for preparing a wear-resistant cable material according to claim 2, characterized in that: In step S4, the ratio of the amount of intermediate 2, N,N-dimethylformamide, intermediate 3, and azobisisobutyronitrile is 1 g:100 mL:5.1 g:0.2 g.
7. The method for preparing a wear-resistant cable material according to claim 1, characterized in that: The raw materials are calculated in parts by weight as follows: 80-100 parts of polypropylene resin, 12-28 parts of modified nano silicon dioxide, 15-25 parts of glass fiber, and 3-5 parts of lubricant.
8. The method for preparing a wear-resistant cable material according to claim 1, characterized in that: The lubricant is one of magnesium stearate and zinc stearate.
Citation Information
Cited By
Polyester FDY (fully drawn yarn) oiling agent with high-concentration emulsion
CN121183461A
Impact-resistant and high-temperature-resistant PE pipe and preparation method thereof
CN121226883A